A facile and efficient [4 + 2] annulation reaction of sulfur ylides: access to N-fused benzimidazoles. Issue 2 (7th December 2018) - Qin, Hui; Miao, Yuanyuan; Xu, Jian; Bi, Qirui; Qu, Wei; Liu, Wenyuan; Feng, Feng; Sun, Haopeng
Abstract : The synthesis of N-fused benzimidazoles via sulfur ylides is first reported. The reaction system is facile and mild without a metal catalyst. Abstract : A facile and efficient approach to synthesize a series of new N-fused benzimidazoles in good yield is reported for the first time using the [4 + 2] cascade cycloaddition of 2-substituted benzimidazole derivatives and a bromoethylsulfonium salt, which is easily prepared on a large scale and is stably crystalline, under mild reaction conditions.